Pelatihan E-Commerce Untuk Mendorong Terwujudnya Wirausaha Santri Pada Yayasan ASWAJA Nusantara, Sleman, Yogyakarta - Mellisa Fitri Andriyani Muzakir; Maisaroh Maisaroh; Tatik Tatik (Jurnal Abdimas Madani dan Lestari (JAMALI), 2022)
Aswaja Nusantara Foundation is a foundation engaged in education and community assistance. This fooundation houses the Aswaja Nusantara Islamic Boarding Shool, Which has 130 students. In addition to studying religion, student at Aswaja Nusantara Islamic Boarding Shcool are also provided with knowledge, one of which is entrepreneurship. The Aswaja Nusantara Foundation Specifically providessupport and attention to student for entrepreneurshipprogrram. There are three problems faced in the santri entrepreneurship, namely the lack of entrepreneurial motivation and entrepreneurial skills possessed, difficulties in the marketing, and mastery of internet technology for business which is still zero. This service aim to provide skills in the use of e-commerce in business world, so that students are able to have the skills and are able to utilize e-commerce applications to support  students entrepreneurs. The method use in the service program is e-commerce training and media creation assistance for marketing student’s products. The target of the program is 25 participants consisting of Aswaja Nusantara students, representatives of student from nearby Islamic boarding schools, micro enterprises fostered by Aswaja Nusantara Foundation. At the end of the program, participants are expected to master the application of e-commerce technology and motivate the to apply it in their start-up business.